Osteonecrosis in a Patient with Crohn's Disease Unrelated to Corticosteroid Use. (1st November 2001) - Khan, Ali; Illiffe, Gerald; Houston, Donald S; Bernstein, Charles N
Abstract : Osteonecrosis is a feared complication of corticosteroid use. However, a direct association between corticosteroid use and osteonecrosis has never been proven. The present report examines the case of a patient with longstanding Crohn's disease who had never been treated with corticosteroids and who developed osteonecrosis of the talus. The association of systemic inflammatory disorders with osteonecrosis and the possible association with vascular thrombosis are discussed.